ANALYSIS OF TENSILE AND FLEXURAL STRENGTH OF HDPE MATERIAL JOINTS IN SHIP CONSTRUCTION - Wibawa, I Putu Arta; Wijaya, Razzaqi Akbar Ilham; Abdullah, Kharis; Wulandari, Kiki Dwi; Sumardiono, Sumardiono; Widodo, Eriek Wahyu Restu; Gafur, Abdul (Journal of Applied Engineering Science, 2023)
The use of wood as the primary material in the fishing vessels construction has been use a lot in Indonesia. At present, there is a problem in the availability of wood materials which are increasingly difficult to obtain. For this reason, it is necessary to innovate good quality wood substitute materials. In this case, HDPE (High-Density Polyethylene) material is the suitable alternative as a substitute for the primary material for fishing vessels. However, further studies are needed due to the lack of regulation and research related to the joint of HDPE materials in ships construction. This study aims to determine the quality of various variations in tensile and bending strength. The method used is experimentation and data processing, while the research variation is V-Seam and X-Seam with hot gas and extrusion welding. Data were obtained by conducting tensile testing with the BS EN 12814-1-2000 standard and bending testing with the BS EN 12814-2-2000 standard. The study's results found that the seam and connection method affect the tensile strength and bending of the HDPE welding joint. The tensile and bending strengths for each variation of V-Seam hot gas, X-Seam hot gas and V-Seam extrusion welding are 14.07 MPa, 15.44 MPa, and 19.29 MPa, while the bending strengths are 29.22 MPa, 33.28 MPa, and 37.85 MPa, so the most optimum tensile and bending strength is obtained from the variation of the V-Seam extrusion welding joint with values of 19.29 MPa and 37.85 MPa, respectively.
Keywords: HDPE, fishing vessels, tensile, bending, welding